Initialdiagnosis of the Association of Milk producers of the family agriculture of Poço das Trincheiras - AL (Agroleite) / Diagnóstico Socioeconômico da Associação dos Produtores de Leite da Agricultura Familiar de Poço das Trincheiras - AL (Agroleite) - Ideginaldo Rogerio da Costa Correia; Bruna Missyelle Bras de Oliveira; Cleyton de Almeida Araújo; Deneson Oliveira Lima; Edilene da Silva Santos; Conceição Maria Dias de Lima (Universidade Estadual de Alagoas, 2019)
Milk cattle breeding plays a key role in the economic and social development of mankind. Aiming at this, the objective was to evaluate the socioeconomic conditions of the Association of Milk Producers of the Family Agriculture of Poço das Trincheiras- AL (Agroleite). The association is made up of thirty-three producers. The methodology using the case study, using data secondary from for the "Full Bucket" project in the care of the cattle producers of milk in the period from January to March 2015. An interesting factor is that all of the interviewees have more than ten years of experience in the activity. Sanitary management has proved a negative point in the properties because the animals are not submitted to vaccination of some illnesses. Another interesting factor is that all of the producers do not use the caatinga, that is, the native pasture in periods of drought. An important point is the lack of application of biotechnology related to animal reproduction.